Sex differences in psychiatric comorbidity and clinical presentation in youths with conduct disorder. (19th May 2021) - Konrad, Kerstin; Kohls, Gregor; Baumann, Sarah; Bernhard, Anka; Martinelli, Anne; Ackermann, Katharina; Smaragdi, Areti; Gonzalez‐Madruga, Karen; Wells, Amy; Rogers, Jack C.; Pauli, Ruth; Clanton, Roberta; et al.
Abstract : Background: Conduct disorder (CD) rarely occurs alone but is typically accompanied by comorbid psychiatric disorders, which complicates the clinical presentation and treatment of affected youths. The aim of this study was to investigate sex differences in comorbidity pattern in CD and to systematically explore the 'gender paradox' and 'delayed‐onset pathway' hypotheses of female CD. Methods: As part of the FemNAT‐CD multisite study, semistructured clinical interviews and rating scales were used to perform a comprehensive phenotypic characterization of 454 girls and 295 boys with CD (9–18 years), compared to 864 sex‐ and age‐matched typically developing controls. Results: Girls with CD exhibited higher rates of current major depression, anxiety disorders, post‐traumatic stress disorder and borderline personality disorder, whereas boys with CD had higher rates of current attention‐deficit/hyperactivity disorder. In line with the 'gender paradox' hypothesis, relative to boys, girls with CD showed significantly more lifetime psychiatric comorbidities (incl. Alcohol Use Disorder), which were accompanied by more severe CD symptoms. Female and male youths with CD also differed significantly in their CD symptom profiles and distribution of age‐of‐onset subtypes of CD (i.e. fewer girls with childhood‐onset CD). In line with the 'delayed‐onset pathway' hypothesis, girls with adolescent‐onset CD showed similar levels of dimensional psychopathology like boys with childhood‐onset CD, while boys with adolescent‐onset CD had the lowest levels of internalizing psychopathology. Conclusions: Within the largest study of CD in girls performed to date, we found compelling evidence for sex differences in comorbidity patterns and clinical presentation of CD. Our findings further support aspects of the 'gender paradox' and 'delayed‐onset pathway' hypotheses by showing that girls with CD had higher rates of comorbid lifetime mental disorders and functional impairments, and they usually developed CD during adolescence. These novel data on sex‐specific clinical profiles of CD will be critical in informing intervention and prevention programmes.